#TITLE_ALTERNATIVE# - Pahrudin (NIM 104 00 012), Ade
Abstract: Multiple wave was a reflection phenomenon in seismic data besides primary wave reflection. Multiple wave has always been a serious problem in seiscmic data processing, since multiple energy often destructively interfere with primary energy. Multiple reflection can be reflected between subsurface reflectors or the surface more than once before being received on the surface. Low velocity contrast at subsurface cause multiple reflection, in the other hand there is a negative reflection coefficient. Generally, primary and multiple could be discriminated base on the different of moveout and velocity. After applying NMO on input data, primaries become flattened, but multiples have residual moveout increasing with offset. In velocity spectrum, multiples have lower velocity than primaries. Some methods have been developed to separate primary wave and multiple to obtain a good picture of seismic data, especially Radon transform and F-K filter. These methods are usually used to remove multiples. Both of the methods will used to separate multiples and primaries reflection, also to investigate abilities of the methods to remove multiples. Radon transform works to moves data between T-X (time-offset) domain and t-ρ (intercept time-ray parameter) domain, and F-K filter moves between T-X (time-offset) domain and f-k (frequency-wavenumber) domain. In act of determining parameter for each method that seen in semblace had an influence to increase primary focus energy.The methods is useful for multiples suppression, but still left the residual multiples. The method of Radon transform is better in multiples suppression than F-K filter.